Analyses of magnetic properties fluctuation in conventional grain oriented silicon steels containing copper - YANG Ping; WANG Zi-liang; LIU Gong-tao; SHEN Xue-mei; BO Dan-qing; MAO Wei-min; TANG Shu-guang (工程科学学报, 2018)
The conventional grain-oriented (CGO) silicon steel containing copper is a type of grain-oriented steel with low cost and high productivity. The processing parameters in CGO steels are quite different to those of low temperature heating and nitriding high permeability (HiB) grain oriented silicon steels, the fluctuation range of the magnetic properties in CGO is much higher than that of nitrided HiB steels. In this study, typical final sheets from production lines of CGO steels containing copper during early stage production were collected, and the structure, texture, and magnetic properties were determined and compared to establish a relationship between the structure of the steels and inhibitors and to elucidate the reasons for property fluctuation. The results indicate that the macrostructure in the final sheets has a relationship with inhibitors and that the grain sizes do not show monotonous behavior. In addition, the defective microstructure in hot-rolled bands and intermediately annealed sheets are investigated and a coarse grain region and a decarburized surface layer are observed. Such regions are considered to influence the inhibitor distribution and impact the fluctuation in structure and its properties.